Education as a Path to Rehabilitation: Challenges and Prospects in the Juvenile Rehabilitation Facility Class II A Bengkulu, Indonesia - Pasmawati, Hermi; Badeni, Badeni; Dharmayana, I Wayan; Pertiwi, Yuliani; Sari, Widya Kartika (Universitas Negeri Padang, 2024)
Education plays a pivotal role in the rehabilitation of juvenile offenders. This qualitative study explores the opportunities and challenges of reforming rehabilitation through formal education at the Youth Rehabilitation Center Class II A Bengkulu. The program aims to enhance academic skills, life competencies, and self-esteem among juvenile offenders. Using a purposive sampling method, the study involved 14 informants, including a head of education and community guidance, a teacher, and 12 foster children. Data were collected through interviews, observations, and document analysis, and analyzed using the Miles and Huberman model. Findings reveal that educational initiatives at the center significantly boost foster children's confidence, motivation, and optimism about their future. The institution's strategic location, dedicated educators, and adequate infrastructure support these efforts. However, several challenges persist, such as limited cooperation from the children’s previous schools, insufficient facilities, a lack of subject-specific resources (e.g., science), and a shortage of qualified teachers. This study provides a detailed analysis of integrating formal education into rehabilitation programs and offers recommendations for improving the quality of educational services in juvenile rehabilitation centers. These insights aim to support the development of inclusive, sustainable, and education-focused rehabilitation policies.